Analysis of Misconception through CRI (Certainty of Response Index) Method among Physics Education Students - Hajar, Siti; Isra, Hutry Handayani; Silaban, Adeline; Akbar, Muhammad (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the level of misconceptions that occur in Cenderawasih University physics education students in the material Temperature, Heat and Waves. This research is a descriptive research conducted in physics department of Cendrawasih University by involving 22 physics education students. The data collection technique used was a test in the form of multiple choice questions of 30 items. The questions were distributed to students and then the results were analyzed by using the Certainty Of Response Index (CRI) method to be categorized into four levels, one of which is misconception category. The results of the study revealed that students experience misconception in the three materials analyzed with the average percentage of students who experienced misconception in the material of Temperature, Heat, and Waves are 20.7% (low category), and 17,61% (low category), and 32.12% (moderate category), respectively. One of the factors causing misconceptions is the lack of understanding and references from educators. Therefore, it is expected that the physics materials is delivered clearly based on the concept so that students can avoid misconceptions.